2021
DOI: 10.32404/rean.v8i2.5526
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Lettuce Submitted to the Rock Dust Remineralizer and Doses of Efficient Microorganisms

Abstract: The use of soil remineralizers with efficient microorganisms (EM) can represent an effective and sustainable alternative to improve the growth, development, and yield of cultivated plants. Thus, the present study aimed to evaluate the effect of different doses of EM, in the presence or absence of rock dust (RD), on the development of iceberg lettuce, cultivar Lucy Brown. The design used was completely randomized, arranged in a 2 x 5 factorial scheme, with four replications. The treatments consisted of the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…These results demonstrated that the vermiculite mining residue, associated with organic matter and/or beneficial microrganisms, was not able to fully replace the soluble sources of nutrients, as has been observed in other studies (Sousa et al, 2021;Almeida et al, 2022). However, these materials can improve the performance of plants compared to non-fertilized plants, possibly by replacing part of the mineral fertilizer that would be provided by soluble sources (Curtis et al, 2023).…”
Section: Resultssupporting
confidence: 77%
“…These results demonstrated that the vermiculite mining residue, associated with organic matter and/or beneficial microrganisms, was not able to fully replace the soluble sources of nutrients, as has been observed in other studies (Sousa et al, 2021;Almeida et al, 2022). However, these materials can improve the performance of plants compared to non-fertilized plants, possibly by replacing part of the mineral fertilizer that would be provided by soluble sources (Curtis et al, 2023).…”
Section: Resultssupporting
confidence: 77%